Ozone enhances biodegradability of heavy hydrocarbons in soil. Issue 1 (June 2016) - Chen, Tengfei; Delgado, Anca G.; Yavuz, Burcu M.; Proctor, Alan J.; Maldonado, Juan; Zuo, Yi; Westerhoff, Paul; Krajmalnik-Brown, Rosa; Rittmann, Bruce E.
Abstract : The molecular complexity and the low solubility of petroleum hydrocarbon residuals in weathered soil hinder bioremediation as a clean-up strategy. Pretreatment with advanced oxidation, such as with ozone gas (O3 ), is a means to transform recalcitrant organics to more biodegradable forms. The efficacy of gas-phase ozone for enhancing the biodegradability of heavy residual petroleum hydrocarbons in weathered soil was tested. Ozonating soil containing ∼1% (w/w) residual petroleum hydrocarbons with a dose of 6 kg ozone/kg initial total petroleum hydrocarbons (TPHs) achieved nearly 50% TPH reduction, simultaneous with a >20-fold increase in soluble chemical oxygen demand, but with a ≤12% loss of total organic carbon. TPH molecules were converted to partly oxidised products, ten of which were identified as n -monocarboxylic acids, which were readily biodegraded, and ozonation resulted in a fourfold increase in 5-d biochemical oxygen demand ( B OD5 ). B OD5 results after ozonation were the same with or without a microbial seed, which suggests that bioaugmentation is likely not necessary after ozonation. Deoxyribonucleic acid sequencing over the time course of the B OD5 tests showed increased diversity and changes in predominant genera, both of which underscore that ozonation made the heavy hydrocarbons readily biodegradable for soil bacteria.